Anthropological Dimension of the Philosophical "Literature-Centric" Model of Ukrainian Romanticism - Z. O. Yankovska; L. V. Sorochuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Romanticism as a movement developed in Germany, where, becoming the philosophy of time in the 18th-19th centuries, spread to all European countries. The "mobility" of the Romantic doctrine, its diversity, sometimes contradictory views, attitude to man as a free, harmonious, creative person led to the susceptibility of this movement by ethnic groups, different in nature and mentality. Its ideas found a wide response in Ukraine with its "cordocentric" type of culture in the early nineteenth century. Since the peculiarity of "Ukrainian Romanticism" was its "literary-centric" nature, the purpose of this study is to analyse and comprehend the place of man in the national philosophy and literature of this period. Accordingly, the main tasks of the work are as follows: to determine the main features, the nature of Ukrainian Romanticism; to trace the main vectors of comprehension and image of man in the literature of this time. Theoretical basis. The ideas of European Romanticism (as a philosophical-historical and general cultural movement) were creatively rethought and assimilated during the emergence of new Ukrainian literature. It provided samples of highly artistic works, unique names of talented writers – creators and thinkers, who in their works reflected the philosophy of time. Based on the works of F. Schlegel, partly E. Husserl, M. Heidegger, K. Jaspers, Romanticism in the Ukrainian humanities, in terms of philosophy, culturology, as well as at the intersection with literature, was studied by T. Bovsunivska, Y. Hrybkova, S. Efremov, N. Kalenichenko, S. Kozak, T. Komarynets, D. Nalyvayko, Y. Nakhlik, I. Ogorodnyk, V. Ogorodnyk, A. Sinitsyna, D. Chyzhevsky, M. Yatsenko, E. Kyryliuk, M. Biletsky, D. Dontsov, S. Efremov, G. Kostyuk, S. Krymsky, Y. Sherekh and others. Originality. The authors of the article prove that Romanticism in Ukraine, being "literary-centric" inherently, having absorbed the main ideas and features of European Romanticism, has its own features and vectors of formation and development. Man in this kind of movement, thanks to the means of art, appears very clearly as a spiritually rich, sensitive, vulnerable and strong person. For him or her, the highest value is freedom, the ability to make freely independent fateful decisions. Conclusions. Ukrainian writers, reflecting the philosophical ideas of Romanticism, saw in man a harmonious combination of "natural" and "social", through which he indirectly carries out his own national existence. In addition to the objective realities of the external world, in their works, Romantic writers appeal to the subjective, internal, spiritual, "ideal" world of the hero, who interacts with reality through his own system of values. At each level of development of the humanities and methodology of cognition, this allows a new reading of these works.